2015
DOI: 10.3390/su7079574
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors that Influence the Willingness to Pay for Irrigation Water in the Kurdistan Regional Government, Iraq

Abstract: Abstract:Water availability has become a problem in many countries of the world. Water scarcity can be economic or physical. Agricultural water use accounts for about three quarters of total global consumption; in many developing countries, irrigation represents over 90% of the water used. The purpose of this paper is to explore the willingness to pay for irrigation water among the farmers from the boundaries governed by the Kurdistan Regional Government (KRG). During the field study, 236 farmers from KRG were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 14 publications
(12 reference statements)
2
19
0
Order By: Relevance
“…In any case, evaluating the willingness to pay for irrigation water can supply beneficial information to policy decision-makers [44]. Such evaluations can provide decisions with valuable information that might be used in the implementation of formulating strategy in water management.…”
Section: Discussionmentioning
confidence: 99%
“…In any case, evaluating the willingness to pay for irrigation water can supply beneficial information to policy decision-makers [44]. Such evaluations can provide decisions with valuable information that might be used in the implementation of formulating strategy in water management.…”
Section: Discussionmentioning
confidence: 99%
“…However, our findings conform to what Mezgebo and Ewnetu, [38] found in Mutale Local Municipality, South Africa which showed that the respondents of age above 50 years were less willing to pay more for improved water services in the short term. On the contrary, Harun et al [39] in a study done in Iraq found that older people were willing to pay more for water irrigation than the young farmers. Again, we found that education is widely considered to be the most important form of human capital [31] and can significantly influence communities WTP.…”
Section: Discussionmentioning
confidence: 93%
“…The CV technique has been very widely applied in the literature to obtain the WTP for non-market goods [16,17] and environmental goods [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Refer to Carson and Hanemann [34] for a better understanding of the CV technique and its implementation.…”
Section: The Methods Of Investigating the Public Acceptability Of Intrmentioning
confidence: 99%